GUBUK GEGANA (GERAKAN GREEN AMONIASI) SEBAGAI SOLUSI KEKURANGAN HIJAUAN DI DAERAH KEBUMEN - Wahyuningsih, Putri; Muslikhatun, Siti; Fiftiyanti, Yulia; Nurhayati, Isti (Ditlitabmas, Ditjen DIKTI, Kemdikbud RI, 2013)
This article discusses about âGubuk Geganaâ, that is a place which is used for ammonia process called amoniasi. This has a result a fodder from straw which has higher nutrition value than usual. Gubuk Gegana is expected to overcome the problem of shortage of fodderÂ in the dry season in Kebumen. Besides, Gubuk Gegana is designed to make the best possible use of many natural potential and develop the knowledge and skills of the society in Kebumen. On the other word, Amoniasi is expected to solve agricultural wastes problem especially rice straw be more optimal utilization.